The Spirit-Led Leader: Nine Leadership Practices and Soul Principles - Geoffrion, Timothy C. (Rowman & Littlefield Publishers, 2005)
In our postmodern, experience-oriented culture, people are longing for greater authenticity, integrity, and depth in their pastors and leaders. Board directors, church members, and staff alike are all eagerly seeking leaders who effectively integrate their spirituality and leadership. Pastors and executives, however, often struggle with knowing how to integrate their spiritual values and practices into their leadership and management roles. Designed for pastors, executives, administrators, managers, coordinators, and all who see themselves as leaders and who want to fulfill their God-given purpose, The Spirit-Led Leader addresses the critical fusion of spiritual life and leadership for those who not only want to see results, but who also desire to care just as deeply about who they are and how they lead as they do about what they produce and accomplish. Geoffrion creates a new vision for spiritual leadership as partly an art, partly a result of careful planning, and always a working of the grace of God